TREN PENELITIAN BERPIKIR KOMPUTASI PADA PEMBELAJARAN MATEMATIKA: ANALISIS BIBLIOMETRIK - Inuhan, Michael; Lekitoo, John Nandito; Romsery, Adelia; Wariaka, Fransiska; Tetiwar, Alberthina (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2025)
This study aims to analyze the global trend of computational thinking research in mathematics learning through a bibliometric approach. The analysis was conducted on 536 documents retrieved from the Scopus database during the period 2007–2024 using the PRISMA method and analyzed through RStudio and VOSviewer software. The results show an average increase in publication trends of 31.04% each year, with the largest contribution coming from Vanderbilt University and the dominance of publications by authors from the United States. The most prolific source is the ACM International Conference Proceeding Series with influential authors include Gautam Biswas and Shuchi Grover. Keyword mapping revealed six main thematic clusters, focusing on computational thinking integration, digital tools, and its relationship with mathematics and STEM education. Five emerging keywords were identified—systematic review, GeoGebra, CT-Tools, mathematics lesson, and ChatGPT—signaling new directions for future research.